1988
DOI: 10.1002/art.1780310217
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis in patients with psoriasis is associated with an immunoglobulin gene polymorphism

Abstract: Sst I, we detected a particular polymorphic DNA pattern in 17 of 28 patients (60.7%) with psoriatic arthropathy but in only 5 of 41 patients (12.2%) with psoriasis alone. Our findings suggest that genes in the immunoglobulin region confer susceptibility to the development of arthropathy in patients with psoriasis.Studies of families have shown that genetic factors play a major role in the development of psoriasis without arthropathy (PS) ( I ) and a less important role in the development of psoriatic arthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Although unusual, nonimmune neurological functions can be proposed, the implication of immune system genes (e.g., HLA-haplotype association and SH linkage) suggests an immunopathology in both the narcoleptic canines and humans. This condition would be consistent with the observed relationships in humans between HLA-associated autoimmune diseases and immunoglobulin heavy-chain polymorphisms (22)(23)(24)(25)(26)(27)(28)(29)(30). Involvement of immune mechanisms in the pathophysiology of narcolepsy and, by logical extension, in control of rapid-eye-movement sleep has been suggested previously (3,(6)(7)(8)(9).…”
Section: Methodssupporting
confidence: 86%
“…Although unusual, nonimmune neurological functions can be proposed, the implication of immune system genes (e.g., HLA-haplotype association and SH linkage) suggests an immunopathology in both the narcoleptic canines and humans. This condition would be consistent with the observed relationships in humans between HLA-associated autoimmune diseases and immunoglobulin heavy-chain polymorphisms (22)(23)(24)(25)(26)(27)(28)(29)(30). Involvement of immune mechanisms in the pathophysiology of narcolepsy and, by logical extension, in control of rapid-eye-movement sleep has been suggested previously (3,(6)(7)(8)(9).…”
Section: Methodssupporting
confidence: 86%
“…The absence of the restriction fragment was observed to be significantly associated with the disease among SLE patients from multiplex families (RR = 9.0) and among randomly selected SLE patients (RR = 7.0) from Mexico. Unaffected family members of Mexican SLE patients were also observed to lack the 3.0-kb fragment more frequently than healthy Mexican controls (RR = 3.8 Other studies have also suggested that immunoglobulin heavy chain constant-region genes may contribute to the expression of SLE (1-4), and immunoglobulin heavy chain constant-region gene RFLPs have been associated with disease susceptibility in multiple sclerosis (18), rheumatoid arthritis (19), and psoriatic arthritis (20). An interactive effect between the major histocompatibility complex and immunoglobulin genes, which may increase susceptibility to SLE, has been proposed (3,4).…”
Section: Discussionmentioning
confidence: 98%
“…The Other studies have also suggested that immunoglobulin heavy chain constant-region genes may contribute to the expression of SLE (1-4), and immunoglobulin heavy chain constant-region gene RFLPs have been associated with disease susceptibility in multiple sclerosis (18), rheumatoid arthritis (19), and psoriatic arthritis (20). An interactive effect between the major histocompatibility complex and immunoglobulin genes, which may increase susceptibility to SLE, has been proposed (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…However, the same group found no association in an Italian cohort of 55 PsA patients. 105,106 Interleukin (IL) 1 is a cytokine secreted by monocytes and macrophages, and its biological effects are controlled by a number of interacting receptors and antagonists. The genes encoding IL-1α, IL-1 , IL-1R1, and IL-1ra loci are located as a cluster on chromosome 2q12-13.…”
Section: Psa and The Non-hla Regions Outside The Mhc Regionmentioning
confidence: 99%